An FDA approved salivary test for SARS-CoV-2 infection - Brooks, Andrew (Henry Stewart Talks, 2020)
Overview of the saliva SARS-COV-2 test, Benefits of this diagnostic test, Test development and accuracy, Manufacturing capabilities